A Validated UV-Spectrophotometric Method for the Estimation of Tinidazole in Bulk and Pharmaceutical Dosage Form - Kothapalli, Umadevi (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT:A new, simple, precise and accurate method for the estimation of Tinidazole in bulk and pharmaceutical dosage forms has been developed. 0.1N HCl was chosen as the solvent system. The Î»max was found to be 278nm. The responses were linear in the range of 10-80Âµg/ml. The regression equation of the calibration graph and correlation coefficient were found to be y = 0.026x - 0.042 and 0.999 respectively. Validation of the method was done in order to demonstrate accuracy, precision, interday and intraday assay, robustness and ruggedness of the proposed method. The %RSD values for both intraday and interday precision were less than 1%. The recovery of the drug from the sample was ranged between 99.12% and 100.96%. Commercial tablets containing 500mg and 300mg of Tinidazole (COZIT and TINA respectively) were analyzed by the proposed method and the results were well within the claimed limits.